Charitable Giving Amidst the COVID-19 Pandemic: A Philippine Context - Tan, Rosalina (Archīum Ateneo, 2023)
This paper presents the results of a survey on altruism amidst economic difficulties during the coronavirus disease (COVID-19) pandemic. The study looked at two cases of charitable giving: (1) intention to donate to a non-government COVID-19 vaccination program, and (2) food donation to a community pantry. A two-stage regression procedure was undertaken to identify the factors affecting the willingness to contribute to a vaccination program (first stage: binary logit regression) and the contribution amount (second stage: ordinary least squares). The binary logit regression was likewise used to identify donors’ characteristics for the community pantries. The survey was conducted among 508 household heads in Metro Manila, Philippines in December 2021 using a multi-stage stratified sampling procedure. First, the study found that the proportion of respondents who expressed willingness to donate to a vaccination program is higher than the proportion of respondents who donated food to a community pantry, which could be due to the benefits (general reduction in the risk of contracting COVID-19) that donors also stood to gain from their contributions. Second, a past act of giving to a community pantry is not a robust predictor of donating to a vaccination program, implying that the decision to give depends on the specific charitable program, as supported by differing sets of robust predictors for the vaccination program (economic-related factors) and the community pantry (religiosity). Third, donating to a non-government COVID-19 vaccination program is income inelastic, implying that the donation is considered a basic consumption item.